Women at the Margins or the Center? Gendered Experiences in Community- Based Tourism in Indonesia - Aisyah, Siti (Advances in Tourism Studies, 2024)
This study explores the gendered dynamics of participation in community-based tourism (CBT) initiatives in Indonesia. Although CBT has been widely promoted as a strategy for sustainable development and local empowerment, gender relations often shape who benefits, who participates, and whose voices are heard in decision-making. Drawing on a qualitative research design, data were collected through semi-structured interviews with women entrepreneurs, homestay operators, craft producers, and community leaders in Lombok and Flores, alongside focus group discussions with mixed-gender community members. Participant observation of daily tourism activities and local meetings provided additional contextual insights. Thematic analysis revealed that women’s involvement in CBT is simultaneously empowering and constraining. On one hand, participation created new income opportunities, enhanced skills, and strengthened women’s social visibility. On the other hand, entrenched gender norms and household responsibilities limited their ability to fully engage in leadership roles or access higher-value segments of tourism. Tensions were particularly evident in negotiations between women’s economic aspirations and cultural expectations of domestic labor. The study concludes that CBT in Indonesia cannot be assumed to be gender-neutral; rather, its outcomes are mediated by local gender relations. Findings offer implications for designing gender-sensitive tourism policies that foster equitable empowerment.